Semiotic Analysis of the H&M Conscious Exclusive A/W20 Advertisement: Exploring Sustainability Issues and Greenwashing Practices - Emillia Della; Naila Oxandiya; Ghanesya Hari Murti; Gullit Tornado Taufan (Journal of Language, Communication, and Tourism, 2025)
This study investigated the sustainability claims of H&M’s Conscious Exclusive A/W20 campaign, focusing on the potential use of greenwashing strategies. The research addressed the gap between the brand’s eco-friendly image and its actual practices. Using Roland Barthes’ semiotic method, the study examined the visual and verbal signs in the advertisement to uncover their denotative and connotative meanings. The findings revealed that while the campaign promoted environmental responsibility through recycled materials, its messages largely served as marketing tools rather than evidence of genuine sustainable practices. It means that there was a gap between the sustainability claims and actual practices in the campaign. The advertisement falls under the category of Green-washed Commercial Advertising, indicating that H&M’s sustainability narrative might be more symbolic than substantive. From the results of this study, it can be concluded that transparency is essential for brands to avoid misleading consumers and to ensure trust in sustainability efforts.